Penerapan Algoritma K-Means Clustering Pada Penjualan Voucer Internet Study Kasus Konter Abc - Mohammad Sabar Jamil; Nugraha Yudhasyah; Hilman Mutaqin; Moh. Milki I. M. (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Rapid technological advances will bring changes to aspects of human life, one of which is how to communicate. With the discovery of cell phones, it is easier for humans to communicate remotely, one of which is WhatsApp. If someone wants to use WhatsApp, internet access is needed so that the sales of internet vouchers are increasing. Data mining is the process of processing data in order to obtain new information, clustering is chosen because it aims to create clusters from existing data. This study aims to cluster internet vouchers so that counter owners can make stock vouchers more precisely. The results of this study yielded the highest value for cluster C1 35,000 while the lowest value for C2 was 43,000 with a total of 99 data with a percentage of 95.19% while cluster C2 consisted of 5 data with a percentage of 4.81%. the conclusion is that the most purchased nominal vouchers are under 40,000. therefore the counter owner can keep more stock for a nominal value below 40,000